Long-term use of somatostatin analogs for chronic gastrointestinal bleeding in hereditary hemorrhagic telangiectasia - Torres-Iglesias, Raquel; Mora-Luján, José María; Iriarte, Adriana; Cerdà, Pau; Alba, Esther; Sánchez-Corral, Miguel Ángel; Berrozpe, Ana; Cruellas, Francesc; Gamundí, Enric; Ribas, Jesús; Castellote, Jose; Riera-Mestre, Antoni (Frontiers in Medicine, 2023)
Background Chronic bleeding due to gastrointestinal (GI) involvement in patients with hemorrhagic hereditary telangiectasia (HHT) can provoke severe anemia with high red blood cells (RBC) transfusion requirements. However, the evidence about how to deal with these patients is scarce. We aimed to assess the long-term efficacy and safety of somatostatin analogs (SA) for anemia management in HHT patients with GI involvement. Methods This is a prospective observational study including patients with HHT and GI involvement attended at a referral center. SA were considered for those patients with chronic anemia. Anemia-related variables were compared in patients receiving SA before and during treatment. Patients receiving SA were divided into responders (patients with minimal hemoglobin levels improvement >10 g/L and maintaining hemoglobin levels ≥80 g/L during treatment), and non-responders. Adverse effects during follow-up were collected. Results Among 119 HHT patients with GI involvement, 67 (56.3%) received SA. These patients showed lower minimal hemoglobin levels (73 [60–87] vs. 99 [70.2–122.5], p < 0.001), and more RBC transfusion requirements (61.2% vs. 38.5%, p = 0.014) than patients without SA therapy. Median treatment period was 20.9 ± 15.2 months. During treatment, there was a statistically significant improvement in minimum hemoglobin levels (94.7 ± 29.8 g/L vs. 74.7 ± 19.7, p < 0.001) and a reduction of patients with minimal hemoglobin levels <80 g/L (39 vs. 61%, p = 0.007) and RBC transfusions requirement (33.9% vs. 59.3%, p < 0.001). Sixteen (23.9%) patients showed mild adverse effects, mostly diarrhea or abdominal pain, leading to treatment discontinuation in 12 (17.9%) patients. Fifty-nine patients were eligible for efficacy assessment and 32 (54.2%) of them were considered responders. Age was associated with non-responder patients, OR 95% CI; 1.070 (1.014–1.130), p = 0.015. Conclusion SA can be considered a long-term effective and safe option for anemia management in HHT patients with GI bleeding. Older age is associated with poorer response.